Children with flat feet have weaker toe grip strength than those having a normal arch - Tashiro, Yuto (J Phys Ther Sci, 2015)
[Purpose] This study investigated the relationship between toe grip strength and foot posture in children. [Subjects and Methods] A total of 619 children participated in this study. The foot posture of the participants was measured using a foot printer and toe grip strength was measured using a toe grip dynamometer. Children were classified into 3 groups; flatfoot, normal, and high arch, according to Staheli’s arch index. The differences in demographic data and toe grip strength among each foot posture group were analyzed by analysis of variance. Additionally, toe grip strength differences were analyzed by analysis of covariance, adjusted to body mass index, age, and gender. [Results] The number of participants classified as flatfoot, normal, and high arch were 110 (17.8%), 468 (75.6%), and 41 (6.6%), respectively. The toe grip strength of flatfoot children was significantly lower than in normal children, as shown by both analysis of variance and analysis of covariance. [Conclusion] A significant difference was detected in toe grip strength between the low arch and normal foot groups. Therefore, it is suggested that training to increase toe grip strength during childhood may prevent the formation of flat feet or help in the development of arch.